Stressful Presentations: Mild Cold Stress in Laboratory Mice Influences Phenotype of Dendritic Cells in Naïve and Tumor-Bearing Mice - Kokolus, Kathleen M.; Spangler, Haley M.; Povinelli, Benjamin J.; Farren, Matthew R.; Lee, Kelvin P.; Repasky, Elizabeth A. (Frontiers in Immunology, 2014)
The ability of dendritic cells (DCs) to stimulate and regulate T cells is critical to effective anti-tumor immunity. Therefore, it is important to fully recognize any inherent factors which may influence DC function under experimental conditions, especially in laboratory mice since they are used so heavily to model immune responses. The goals of this report are to 1) briefly summarize previous work revealing how DCs respond to various forms of physiological stress and 2) to present new data highlighting the potential for chronic mild cold stress inherent to mice housed at the required standard ambient temperatures to influence baseline DCs properties in naïve and tumor-bearing mice. As recent data from our group shows that CD8+ T cell function is significantly altered by chronic mild cold stress and since DC function is crucial for CD8+ T cell activation, we wondered whether housing temperature may also be influencing DC function. Here we report that there are several significant phenotypical and functional differences among DC subsets in naïve and tumor-bearing mice housed at either standard housing temperature or at a thermoneutral ambient temperature, which significantly reduces the extent of cold stress. The new data presented here strongly suggests that, by itself, the housing temperature of mice can affect fundamental properties and functions of DCs. Therefore differences in basal levels of stress due to housing should be taken into consideration when interpreting experiments designed to evaluate the impact of additional variables, including other stressors on DC function.